Patterns of development of retinal vascular pathology at remote time period after radiation exposure - Fedirko, P. A.; Garkava, N.A. (Ukrainian Journal of Ophthalmology, 2026)
Background. Retinal vascular system is extremely sensitive to ionizing radiation exposure and requires priority medical examination. Probability of new accident environmental contamination with radioactive material is a factor that makes us draw a lesson from Chornobyl in details. The purpose of the present study was to analyze regularities in development of retinal vascular pathology at remote time period after radiation exposure. Material and Methods. We used results of long-term follow-up of two cohorts of participants of the liquidation of Chernobyl NPP accident consequences (Chornobyl liquidators) in 1986-1987. The first cohort included 5 195 Chornobyl liquidators, follow-up period 1992-2004; the second cohort included 2 892 Chornobyl liquidators, follow-up period 1988-2001. Results. Retinal angiopathy was shown to be the most common eye disease in radiation exposed patients at remote time period after ionizing radiation exposure and to have specific characteristics. Angiopathy development risk depends on age, stay-at-risk time and radiation dose; significant risk excess can occur at 4-5 years after radiation exposure. Incidence reached its maximum at 9 years after radiation exposure, followed by a slight incidence decrease with a re-increase in next 4 years. Conclusion. Pathology of retinal vessels is the most common eye disease in radiation exposed persons and can develop as early as 4-5 years after radiation exposure. The main risk factors for its development are age and external radiation dose. Primary angiopathy incidence reached the first maximum at 9 years with re-increase at 13 years after radiation exposure.